1997
DOI: 10.1152/jappl.1997.83.3.792
|View full text |Cite
|
Sign up to set email alerts
|

RTN TRH causes prolonged respiratory stimulation

Abstract: We injected thyrotropin-releasing hormone (TRH; 10 nl; 0.25, 0.5, 1.0, or 10 mM), its inactive free acid form (TRHOH; 1 mM), or a metabolite with low TRH-receptor binding affinity, histidine-proline diketopiperazine (cHP; 1 mM), into the retrotrapezoid nucleus of anesthetized rats. Injection location was verified by anatomic analysis. Lower doses (0.25-0.5 mM) significantly increased both the product of integrated phrenic amplitude and frequency (Phr . f) and f for 20-30 min compared with artificial cerebrospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…(Li and Nattie, 2002)). Injections of thyrotropin releasing hormone, a substance that activates the ccRTN neurons also activate both phrenic rate and amplitude (Cream et al, 1997) and injections of muscimol into the RTN region reduce breathing frequency in conscious rats, at least transiently (Nattie and Li, 2000). Yet, RTN acidification in conscious and in anesthetized rats stimulate breathing exclusively through an increase in tidal volume (Li and Nattie, 1997; Li et al, 1999).…”
Section: The Ccrtn Neurons Stimulate Inspiratory Motor Activitymentioning
confidence: 99%
“…(Li and Nattie, 2002)). Injections of thyrotropin releasing hormone, a substance that activates the ccRTN neurons also activate both phrenic rate and amplitude (Cream et al, 1997) and injections of muscimol into the RTN region reduce breathing frequency in conscious rats, at least transiently (Nattie and Li, 2000). Yet, RTN acidification in conscious and in anesthetized rats stimulate breathing exclusively through an increase in tidal volume (Li and Nattie, 1997; Li et al, 1999).…”
Section: The Ccrtn Neurons Stimulate Inspiratory Motor Activitymentioning
confidence: 99%
“…There are heavy projections from 5-HT neurons within the medullary raphé nuclei to the major respiratory nuclei, including hypoglossal and phrenic motor neurons (Holtman, Jr. et al, 1984a, 1984b; Connelly et al, 1989; Smith et al, 1989; Thor and Helke, 1989; Henry and Manaker, 1998; Aungst et al, 2008). Exogenous 5-HT, TRH and SP each stimulate respiratory motor output both in vivo and in vitro (Lalley, 1986; Morin et al, 1991; Monteau et al, 1994; Lalley et al, 1995; Hilaire et al, 1997; Cream et al, 1997, 1999; Pena and Ramirez, 2002, 2004; Manzke et al, 2003; Richerson, 2004; Brandes et al, 2006). Stimulation of raphé neurons causes an increase in respiratory output due to release of these transmitters (Lalley et al, 1986; Morin et al, 1990; Aungst et al, 2008), as recently reviewed in detail (Richerson, 2004; Hodges and Richerson, 2008b).…”
Section: Evidence That Serotonergic Neurons Are Respiratory Chemosmentioning
confidence: 99%
“…There is a growing body of evidence that there is an association between TRH and the respiratory system. Injecting TRH into an important component of the rostral ventrolateral medulla, the retrotrapezoid nucleus, of anesthetized rats had powerful stimulatory effects on the product of integrated phrenic amplitude and frequency, and this response was dose-dependent 25. There was an increase in ventilation, O 2 consumption, and body temperature after TRH injection into the retrotrapezoid nucleus in conscious rats, and it was concluded that TRH could have an important role as a state-dependent modulator of breathing control 26.…”
Section: Discussionmentioning
confidence: 98%